Analytical study on effect of groundwater table and rainfall infiltration on the stability and performance of Muar Trial Embankment by using PLAXIS 2D - Sim, M L; Ling, F N L; Zaihasra, A T (2024)
Stability and performance of embankment is crucial throughout its service life especially when subjected to various environment factors namely rainfall and fluctuation of groundwater table. The environmental factors are normally site dependent and vary from time to time. Thus, it is critical to assess the stability and performance of embankment when subjected to environmental factors. The geometry and soil profile of well documented Muar Trial embankment was utilized as base model with the aim to determine the effect of water table and rainfall infiltration on its stability. The impact of these factors on embankment stability is investigated numerically via Plaxis 2D. The findings highlight the importance of considering fully coupled flow-deformation analysis in PLAXIS 2D when simulating rainfall infiltration on the embankment slope. Stability of simulated slopes was determined via strength reduction technique which is known as one of the FEM methods to determine slope stability. The findings showed that the short-term safety factor of slope is slightly increased with 0.4 by taking into consideration possibility of water table raise due to poor drainage. However, simulated 1-day rainfall event didn’t significantly affect the stability of embankment slope. Future work should explore consolidation process after drawdown of water table and incorporating long-term rainfall data to validate the practical assessment of embankment stability in engineering scenarios.